CT imaging manifestations of tuberculous aortic aneurysm - Xing, X.N.; Sun, Zhonghua; Chen, L.; Zhang, N.; Xiong, W.; Li, Y. (MedReviews, 2022)
Background: Tuberculous aortic aneurysm (TBAA) is a rare complication of TB and is associated with high mortality. Early diagnosis is critical; however, it is challenging due to nonspecific symptoms. This study summarized the computed tomography (CT) features of TBAA with the aim of assisting with timely clinical diagnosis. Methods: Seventeen patients with TBAA between 2015 and 2020 were included in this study. The clinical manifestations, past medical history, laboratory and imaging examinations, treatments, and other data were collected and analyzed. CT angiography was performed in all patients. Results: All tuberculous aneurysms were pseudoaneurysms, which were located in the thoracic aorta (8/17, 47%), abdominal aorta (7/17, 41%), junction of the thoracic and abdominal aorta (1/17, 6%) or abdominal aorta and iliac artery (1/17, 6%) region. The shapes of all aneurysms were saccular, and nine of them were lobulated. The aneurysm diameter ranged from 3 to 12 cm. Of the 17 patients, 12 (71%) had calcification; 14 (82%) had intraluminal thrombus; 12 (71%) showed enlarged lymph nodes, which were closely related to the aneurysm; and 9 (52.94%) had tuberculous spondylitis including TB of the thoracic lumbar and lumbosacral spine. Psoas abscess was detected in 4 (23%) patients and iliopsoas abscess was detected in 1 (6%) patient. Conclusions: TBAAs typically show mycotic shapes on CT scans. Another feature is that the surrounding tissues and adjacent organs of tubercular aneurysms are usually infected with TB, and most of them are accompanied by other sites of TB.